'Momma bear wants to protect': Vicarious parenting in practitioners working with disturbed and traumatised children. Issue 4 (9th December 2019) - Fixsen, Alison; Ridge, Damien; Evans, Carys
Abstract: Practitioners working with disturbed and neglected children and young people face many practical and personal challenges, including countertransference and secondary trauma reactions. One underexplored area is the practitioner requirement to negotiate with children's parents and to process feelings towards both parents and children. We explore the experiences of female counsellors and psychologists working with children and young adults in the UK mental health care sector, using an inductive thematic analysis. While participants spoke positively about their vocation and satisfaction gained from acting as an agent of change in young people's lives, they also related highly intense emotional work and traumatic accounts, using powerful metaphors to convey the impact of hearing and processing stories, indicating vicarious trauma effects and a strong parental invocation in therapists, including maternal feelings towards some children ('vicarious parenting'). Some parents were cast as potentially harming a child and obstructing the professional's work. Our paper fleshes out vicarious parenting as a particular form of countertransference.